Pengaruh Efektifitas Influencer Marketing Terhadap Minat Beli Melalui Brand Image Produk Kosmetik Scarlett Whitening Pada Tiktokshop - Rizal, Muhamad Gilang Fachrul; Saputra, Febrian Eko; Muhammad, Mahathir (Jambura Economic Education Journal, 2025)
The purpose of this study is to examine the relationship between influencer marketing and purchase interest in Scarlett Whitening products in Bandar Lampung City as it relates to brand image.  Questionnaires are used to gather data for the quantitative approach.  Scarlett Whitening product users in Bandar Lampung City were the subjects of this study.  Due to the lack of precise population size data, respondents were chosen by purposive selection, a non-probability sample technique, with an emphasis on Gen Z customers who had bought Scarlett Whitening products in Bandar Lampung. Data analysis uses Structural Equation Modeling (SEM) and Partial Least Square (PLS) using SmartPLS as an analysis tool. The results of this study show that all constructs are positively and significantly related to each other. First, Influencer Marketing has a significant influence on Brand Image. Second, Brand Image has a significant influence on Purchase Intention. Third, Influencer Marketing has a significant impact on Purchase Interest. And finally, Brand Image acts as a positive mediator between Influencer Marketing and Purchase Interest. This research can be improved with several suggestions, such as expanding the research area outside Bandar Lampung to get more general results, as well as considering conducting an in-depth analysis of Influencer selection and exploring the impact of Brand Image and Influencer Marketing on consumer choices.